Experimental Characterization and Correlation Analysis of Indoor Channels at 15 GHz - Xin Zhou; Zhangdui Zhong; Bei Zhang; Ruisi He; Ke Guan; Qi Wang; David Matolak (International Journal of Antennas and Propagation)
The indoor radio channels at 15 GHz are investigated based on measurements. The large- and small-scale fading behaviors as well as the delay dispersion characteristics are discussed. It is found that the large-scale fading, Ricean K-factor, and delay spread can be described by log-normal distributions. Furthermore, both autocorrelation and cross correlation properties of the above parameters are analyzed and modeled. These parameters characterize fading and delay behaviors as well as their mutual dependency and can be used as empirical values for future wireless system design and simulation in 15 GHz short-range indoor channels.